The lively accretion disc in NGC 2992 – I. Transient iron K emission lines in the high-flux state. Issue 3 (13th June 2020) - Marinucci, A; Bianchi, S; Braito, V; De Marco, B; Matt, G; Middei, R; Nardini, E; Reeves, J N
ABSTRACT: We report on one of the brightest flux levels of the Seyfert 2 galaxy NGC 2992 ever observed in X-rays, on 2019 May. The source has been monitored every few days from 2019 March 26 to 2019 December 14 by Swift -X-Ray Telescope (XRT), and simultaneous XMM–Newton (250 ks) and NuSTAR (120 ks) observations were triggered on 2019 May 6. The high count rate of the source (its 2–10 keV flux ranged between 0.7 and 1.0 × 10 −10 erg cm −2 s −1 ) allows us to perform a time-resolved spectroscopy, probing spatial scales of tens of gravitational radii from the central black hole. By constructing a map of the excess emission over the primary continuum, we find several emission structures in the 5.0–7.2 keV energy band. From fitting the 50 European Photon Imaging Camera (EPIC)-pn spectral slices of ∼5 ks duration, we interpret them as a constant narrow iron Kα line and three variable components in the iron K complex. When a self-consistent model accounting for the accretion disc emission is considered (KYNrline ), two of these features (in the 5.0–5.8 and 6.8–7.2 keV bands) can be ascribed to a flaring region of the accretion disc located at r in ≃ 15–40 r g from the black hole. The third one (6.5–6.8 keV) is likely produced at much larger radii ( r in > 50 r g ). The inner radius and the azimuthal extension retrieved from the co-added spectra of the flaring states are r in = 15 ± 3 r g and ϕ = 165°–330°, suggesting that the emitting region responsible for the broad iron K component is a relatively compact annular sector within the disc. Our findings support a physical scenario in which the accretion disc in NGC 2992 becomes more active at high accretion rates (L_bol/L_Edd4 per cent).